Nickel-promoted oxidative domino Csp3–H/N–H bond double-isocyanide insertion reaction to construct pyrrolin-2-ones. Issue 13 (16th March 2021) - Wen, Li-Rong; Wang, Ning-Ning; Du, Wu-Bo; Ma, Qiang; Zhang, Lin-Bao; Li, Ming
Abstract : The first nickel-promoted oxidative Csp3 –H/N–H double isocyanide insertion reaction for the synthesis of pyrrolin-2-ones. Abstract : The first nickel-catalyzed oxidative domino Csp3 –H/N–H double isocyanide insertion reaction of acetamides with isocyanides has been developed for the synthesis of pyrrolin-2-one derivatives. A wide range of acetamides bearing various functional groups are compatible with this reaction system by utilizing Ni(acac)2 as a catalyst. In this transformation, isocyanide could serve as a C1 connector and insert into the inactive Csp3 –H bond, representing an effective way to construct heterocycles.